HYBRID NEUROTECHNOLOGIES: INTEGRATING NANOTECHNOLOGY AND NEUROSCIENCE FOR PRECISION TARGETED BRAIN THERAPY AND ADVANCED NEUROTHERAPEUTIC INNOVATION (Global Conference on Medical and Health Sciences, 2026)
Hybrid neurotechnologies represent a rapidly emerging frontier in neuroscience, combining advances in nanotechnology and neural engineering to enable highly precise and targeted brain therapies. The integration of nanoscale materials with neurobiological systems offers unprecedented opportunities for diagnosis, drug delivery, and modulation of neural activity. These technologies aim to overcome traditional limitations in neurological treatment, including poor drug penetration, lack of specificity, and systemic side effects.
Keywords: Hybrid neurotechnologies; Nanotechnology; Brain therapy; Targeted drug delivery; Blood–brain barrier; Neuroengineering; Nanoparticles; Precision medicine